Heterochromatin protein HP1BP3 modulates haematopoiesis and leukemogenesis - Almars, Amany (2021)
Acute myeloid leukaemia (AML) is a heterogeneous malignancy characterized by uncontrolled proliferation of undifferentiated hematopoietic stem/progenitor cells. AML is one of the most comprehensively studied malignancies. Although genetic mutations, particularly chromosomal abnormalities and mutations in known oncogenes, have an integral impact in the development of the disease, increasing evidence suggest the important roles of epigenetic dysregulation on the pathogenesis of AML. Unlike genetic abnormalities, epigenetic alterations are reversible; thus, they can be potential therapeutic targets using specific inhibitors.